Inside Back Cover: A Chemistry for Incorporation of Selenium into DNA‐Encoded Libraries (Angew. Chem. Int. Ed. 32/2020). Issue 32 (14th May 2020) - Xu, Hongtao; Gu, Yuang; Zhang, Shuning; Xiong, Huan; Ma, Fei; Lu, Fengping; Ji, Qun; Liu, Lili; Ma, Peixiang; Hou, Wei; Yang, Guang; Lerner, Richard A.
Abstract : Selenium is an essential trace element named after the Greek goddess of the moon, Selene. In their Research Article on page 13273, W. Hou, G. Yang, R. A. Lerner, and co‐workers introduce benzoselenazolone as a new selenide reagent for on‐DNA C−H selenylation under rhodium(III) catalysis. This work expands the chemical space of DNA‐encoded libraries to selenium‐containing molecules (SeDELs) and lays the foundation for the development of selenium‐containing drugs.